Atrial appendage closure is associated with increased risk for postoperative atrial fibrillation - Jeffrey H. Shuhaiber; Mostafa Abbas; Thomas Morland; H. Lester Kirchner; Yasser El-Manzalawy (Journal of Cardiothoracic Surgery)
Abstract Objectives This study aims to examine the relationship between left atrial appendage closure (LAAC) and post-operative atrial fibrillation (POAF) in cardiac surgery patients with no pre-operative atrial fibrillation (AF). Methods We analyzed a cohort of 2059 adult patients in our Society of Thoracic Surgery (STS) database who underwent at least one of the following procedures between 2018 and 2021: coronary artery bypass grafting (CABG), aortic valve replacement, or mitral valve replacement. All patients had no pre-operative AF, and 169 (8.2%) of them received a left atrial appendage closure (LAAC). Primary outcome was new-onset POAF and secondary outcomes included 1-year mortality, 30-day readmission, 1-year incident stroke, and post-operative hospital length of stay (LOS). Patients without an LAAC were matched to patients with LAAC using a 1:1 nearest neighbor propensity score method to reduce the bias due to potential confounding. Associations between LAAC and postoperative adverse outcomes were assessed using appropriate statistical tests for matched analyses. Results The matched cohort included 162 pairs. LAAC was associated with elevated risk of new-onset POAF (41.4% vs. 25.3%, p = 0.003), and postoperative hospital LOS (142.1 vs. 120.5 h, p = 0.001). The LAAC did not significantly impact all-cause 1-year mortality, 30-day readmission, and 1-year incident stroke. Conclusions In cardiac surgery patients with no pre-operative history AF, LAAC was associated with substantially higher rates of new-onset POAF, without a corresponding impact on risk of 1-year incident stroke, 30-day readmission, or 1-year mortality.